2007
DOI: 10.4188/jte.53.137
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Elastomeric Nanofiber Membranes Produced by Electrospinning

Abstract: This study examines the feasibility of co-electrospinning vapor grown carbon nanofibers (VGNF) within thermoplastic elastomer. The reinforcement effect was studied. The diameter of the thermoplastic elastomer was found to range from 0.5 to 3 μm. The mechanical properties of the electrospun fibrous structure were found to be similar to that of cast elastomeric films. However, the electrospun fibrous membranes have superior tactile properties. The addition of VGNF significantly increases the bulkiness of the fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 13 publications
(10 reference statements)
2
14
0
Order By: Relevance
“…The significant enhancement of adhesion could be explained because the wet electrospun scaffold was produced using the low PES solution concentration (20 wt % and 18 wt %). The nanofiber diameter of 20 wt % PES and 18 wt % PES electrospun webs decreased to 329 nm and 215 nm, respectively, in agreement with the literature relating fiber diameter to polymer solution concentration 41–43. The low viscosity at low solution concentration can also be one of possible causes for the beading phenomenon of the electrospun scaffold at 20 wt % PES solution (Table 1, S5) and coalescence of electrospun web at 18 wt % PES solution (Table 1, S6).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The significant enhancement of adhesion could be explained because the wet electrospun scaffold was produced using the low PES solution concentration (20 wt % and 18 wt %). The nanofiber diameter of 20 wt % PES and 18 wt % PES electrospun webs decreased to 329 nm and 215 nm, respectively, in agreement with the literature relating fiber diameter to polymer solution concentration 41–43. The low viscosity at low solution concentration can also be one of possible causes for the beading phenomenon of the electrospun scaffold at 20 wt % PES solution (Table 1, S5) and coalescence of electrospun web at 18 wt % PES solution (Table 1, S6).…”
Section: Resultssupporting
confidence: 86%
“…The diameter of electrospun nanofibers has been shown to increase with increasing polymer concentration 41–43. It is seen in Table 2 and Figure 2 that as the concentration decreased from 22 wt % to 20 wt %, the nanofibers became thinner but beads began to form within the scaffold.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The Berry's number is defined as the product of intrinsic viscosity and the polymer concentration of the solution. It was found that electrospinnability and fiber diameter can be correlated to the Berry number of the polymers 18. For example, the range of Berry's number for PAN polymer can be divided into four regions, with the first region corresponding to a Berry's number lower than 1, region 2 corresponding to a Berry's number between 1 and 2.7, and region 3 corresponding to 2.7–3.6, whereas region 4 corresponds to a Berry's number of above 3.6.…”
Section: Electrospun Structuresmentioning
confidence: 99%
“…So far, several efforts have been made to increase the production rate of nanofibers. For instance, modified single-needle [17,18], multi-needle [19][20][21][22][23][24][25][26][27], needleless systems [28][29][30][31][32][33][34], a plastic filter set-up [35] and forcespinning have been developed to enhance nanofiber production rate. Forcespinning TM or centrifuge spinning uses centrifugal force, rather than electrostatic force, as in the electrospinning process [36].…”
Section: Introductionmentioning
confidence: 99%